Abiotic pulses and microbial activity lags in greenhouse gas emissions due to tillage. Issue 1 (22nd May 2020) - Duval, Benjamin D.
Abstract: Tillage affects atmosphere–soil greenhouse gas (GHG) flux by opening soil pore spaces releasing pockets of CO2, CH4, and N2 O. Tillage may also stimulate microbes responsible for GHG biogenesis and consumption at longer time scales following a discrete tillage event. I measured soil gas flux immediately after three mechanically different tillage events (moldboard plow, rip‐plow, and disc‐till) over 2 mo within the same field. Delayed effects of tillage on soil respiration were measured; CH4 and N2 O fluxes via laboratory incubations on soils were collected following tillage events compared to undisturbed soils. Moldboard plowing did not result in immediate pulses of GHG. Carbon dioxide emissions and CH4 influx to soil peaked 1 h post‐plow. Later rip‐plowing caused a more sustained pulse of CO2 and CH4 uptake over 2 h in the field. Disc‐tillage produced a CO2 production pulse‐then‐decline profile, but CH4 and N2 O fluxes were highly variable after this event. Greenhouse gas flux from laboratory‐incubated alfalfa soil and fallow soil were similar to soil collected after rip‐plowing. Soils incubated after the last field tillage event produced significantly lower CO2 emissions during lab incubations compared with other undisturbed and plowed soil. These results show that instantaneous tillage effects are not uniform among GHGs, tillage alteration of soil respiration persists for months following a disturbance, and repeated tillage in the field changes microbial regulation of specific GHGs. Tillage has immediate impacts on GHG flux and has the potential for persistent effects on microbial activity that need further investigation as a GHG abatement tool.